LA APERTURA DE INTEGRACIÓN Y LA COOPERACIÓN ECONÓMICA Y COMERCIAL EN EL NUEVO MARCO JURÍDICO DE INTEGRACIÓN DE LA UNASUR - Vega Centeno, Máximo Alfredo Ugarte (2013)
In this new context many claim, from one side, that modernity and democracy come to be inseparable binomials and, for the other side, regional integration as a mechanism to accelerate economic – trade development of developing countries in internal markets, which allow these to integrate with competitiveness in the current globalization of the economy and world trade. In that sense, the new winds blowing through the integration processes, multipolarity, globalization and transnationalization of the world economy, make Latin America have many doubts that can be summarized in two: the insertion and integration in Latin America. The first involves, mainly, external openness, privatization, deregulation of markets and reducing the government intervention. And the second is the concern about if these processes, because of their magnitude, do not have as a result social progress or prosperity for ordinary people.